Influence of porosity on mechanical and corrosion properties of SLM 316L stainless steel - Yang, Dengcui; Kan, Xinfeng; Gao, Pengfei; Zhao, Yan; Yin, Yanjun; Zhao, Zhengzhi; Sun, Jiquan (Applied physics. A, Materials science & processing, 2022)
In this study, 316L stainless steel was fabricated by selective laser melting under different process parameters (375 W–2100 mm·s −1 , 235 W–1400 mm·s −1 , 135 W–750 mm·s −1 ). The solidification microstructure and porosity characteristic of SLM 316L SS samples were researched, and the mechanical and corrosion properties were investigated by subsequent tensile testing and electrochemical testing. It was found that at the same laser energy density, changing the combination of laser power and scanning speed can form different solidified melt pool morphologies. Simultaneously, the development of porosities depends on the melt pool. In the current experimental results, the strength does not seem to noticeable change with the decrease in porosity level and pores size, but it significantly influences ductility. Besides, the pores of SLM 316L SS samples have higher sensitivity to pitting behavior. Under higher porosity level conditions, the as-fabricated sample was more prone to pitting, formed unstable passive film, and easy to be broken down.